Treatment of erectile dysfunction with sildenafil citrate (Viagra) in parkinsonism due to Parkinson's disease or multiple system atrophy with observations on orthostatic hypotension - Hussain, I (BMJ Group, 2001)
OBJECTIVES—To assess the efficacy and safety of sildenafil citrate (Viagra) in men with erectile dysfunction and parkinsonism due either to Parkinson's disease or multiple system atrophy. METHODS—Twenty four patients with erectile disease were recruited, 12 with Parkinson's disease and 12 with multiple system atrophy, into a randomised, double blind, placebo controlled, crossover study of sildenafil citrate. The starting dose was 50 mg active or placebo medication with the opportunity for dose adjustment depending on efficacy and tolerability. The international index of erectile function questionnaire (IIEF) was used to assess treatment efficacy and a quality of life questionnaire to assess the effect of treatment on sex life and whole life. Criteria for entry included a definite neurological diagnosis and a standing systolic blood pressure of 90-180 mm Hg and diastolic blood pressure of 50-110 mm Hg, on treatment if necessary. Blood pressure was taken at randomisation (visit 2) and crossover (visit 5) lying, sitting, and standing, before and 1 hour after taking the study medication in hospital. RESULTS—Sidenafil citrate was efficacious in men with parkinsonism with a significant improvement, as demonstrated in questionnaire responses, in ability to achieve and maintain an erection and improvement in quality of sex life. In Parkinson's disease there was minimal change in blood pressure between active and placebo medication. In multiple system atrophy, six patients were studied before recruitment was stopped because three men showed a severe drop in blood pressure 1 hour after taking the active medication. Two were already known to have orthostatic hypotension and were receiving treatment with ephedrine and midodrine but the third had asymptomatic hypotension. However, the blood pressures in all three had been within the inclusion criterion for the study protocol. Despite a significant postural fall in blood pressure after sildenafil, all patients with multiple system atrophy reported a good erectile response and were reluctant to discontinue the medication. CONCLUSIONS—Sidenafil citrate (50 mg) is efficacious in the treatment of erectile dysfunction in parkinsonism due to Parkinson's disease or multiple system atrophy; however, it may unmask or exacerbate hypotension in multiple system atrophy. As Parkinson's disease may be diagnostically difficult to distinguish from multiple system atrophy, especially in the early stages, we recommend measurement of lying and standing blood pressure before prescribing sildenafil to men with parkinsonism. Furthermore, such patients should be made aware of seeking medical advice if they develop symptoms on treatment suggestive of orthostatic hypotension.